2019
DOI: 10.1002/wer.1101
|View full text |Cite
|
Sign up to set email alerts
|

A reduction in triclosan and triclocarban in water resource recovery facilities’ influent, effluent, and biosolids following the U.S. Food and Drug Administration's 2013 proposed rulemaking on antibacterial products

Abstract: Pharmaceutical and personal care product compounds (PPCPs) comprise a large and diverse group of chemical compounds, including prescription and over‐the‐counter drugs and cleaning agents. Although PPCPs in the effluent and biosolids of water resource recovery facilities (WRRFs) are currently not regulated, public interest has led the Metropolitan Water Reclamation District of Greater Chicago to monitor for 11 PPCPs in the influent, effluent, and biosolids at its seven WRRFs. In 2016, the U.S. Food and Drug Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Implementation of control measures can rapidly reduce loads coming in our wastewater treatment plants. For example, Krogh, Lyons, and Lowe (2017) and Brose et al (2019) (Brose et al, 2019;Krogh et al, 2017) found statistically significant decreases in triclosan and/or triclocarban concentrations in wastewater influent in 2014 compared to previous years, which could be attributed to a policy change by the U.S. FDA affecting the source of these compounds in consumer products. Likewise, Andrade et al (2015) (Andrade et al, 2015) showed a decrease in brominated diphenyl ether (BDE)-47 and BDE-49 concentrations in wastewater influent that could be attributed to the phase-out of these compounds in manufacturing.…”
Section: Discussionmentioning
confidence: 94%
“…Implementation of control measures can rapidly reduce loads coming in our wastewater treatment plants. For example, Krogh, Lyons, and Lowe (2017) and Brose et al (2019) (Brose et al, 2019;Krogh et al, 2017) found statistically significant decreases in triclosan and/or triclocarban concentrations in wastewater influent in 2014 compared to previous years, which could be attributed to a policy change by the U.S. FDA affecting the source of these compounds in consumer products. Likewise, Andrade et al (2015) (Andrade et al, 2015) showed a decrease in brominated diphenyl ether (BDE)-47 and BDE-49 concentrations in wastewater influent that could be attributed to the phase-out of these compounds in manufacturing.…”
Section: Discussionmentioning
confidence: 94%
“…TCC is ranked in the top 10 Contaminant of Emerging Concern (CEC) occurrence. In September 2016, the U.S. Food and Drug Administration banned its use in over-the-counter hand and body washes [15], but this compound still retained a large market demand [16]. More recent studies are devoted to the removal of TCC and its dechlorinated congeners from soil, given their toxicity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Triclosan (2,4,4 -Trichloro-2 -hydroxydiphenyl ether) corresponds to an antimicrobial agent that has been utilized for more than five decades as an antiseptic, disinfectant or preservative in clinical situations and numerous consumer products. TCS has been identified in wastewater treatment plants [1][2][3] and in surface water [4,5]. Recent publications of TCS describe various health effects, including endocrine-disruption, uncoupling mitochondria, among others [6,7].…”
Section: Introductionmentioning
confidence: 99%